BMI Effects on Childhood Motor Skills - Quka, Najada; R, Selenica; G, Quka; LL, Shore (Arena-Journal of Physical Activities, 2020)
Introduction: The development of Motor Skills (Fine and Gross) during childhood is considered essential and very important considering them as â€žbuilding blocksâ€ of their motor development. Educating early motor skill competences are mediatory for children helping them to easily perform different daily movements and more complex influencing on providing an active lifestyle. But unfortunately, the motor skills in obese children seem to be limited as a result of having difficulties controlling their posture during different daily movements. Postural control plays an important role almost at every type of movements, especially over those which are directly influenced by this capacity in the biomechanical aspect. Aim: The goal of this review paper was to investigate the relationship between BMI and Motor Skills in children. Through this study, we wanted to provide other important scientific reasons about the necessity of obesity prevention since childhood period as mediatory of a better lifestyle. Methodology: To successfully realize this review paper we studied and analyzed the contemporary scientific literature provided by various Internet-based research sectors such as â€žJab Refâ€ â€žPub Medâ€ â€žGoogle Scholarâ€ â€žMedlineâ€ â€žSports Discussâ€ and â€žResearch Gateâ€. Results: The results have shown that obese children manifested limited â€žGrossâ€ Motor Skills, which are identified mostly in those motions that BMI negatively impacted on their execution affecting especially their dexterity. This limited situation regarding gross motor skills at obese children result because of difficulties that they have to manage their heavyweight and to keep balance during performing. Unfortunately, the relationship between fine motor skills and BMI continues to be unclear because there are few studies analyzing this relationship and different testing protocols used by them to identify it. Conclusion: At the end of our study, we can say that despite the diverse evidences, BMI may negatively affect especially those Motor Skills (fine & gross) when body weight makes it difficult to maintain balance during motion execution reducing postural control. One of the most important conclusion after all of this review we can strongly emphasize that Physical Activity must be part of everyone daily life for a healthy lifespan. In addition, for obese children, physical activities are mediatory in order to lose weight influencing postural control improvement and better motor skills.